Familiäre Gewalt im Fokus: Fakten - Behandlungsmodelle - Prävention ; Handbuch - Hamel, John; Nicholls, Tonia L.; Amendt, Gerhard; Balzer, Karin; Boly, Anna Maria; Maercker, Paul (Ikaru Verlag, 2015)
Hrsg. d. dt. Ausg.: Gerhard Amendt. Aus d. Amerikan. übers. von Karin Balzer...